Antigypsyism in Portugal: Expressions of hate and racism in social networks - Magano, O.; D’ Oliveira, T. (Social Sciences, 2023)
Portuguese Roma/Ciganos face different forms of negative reactions; they are marginalized, live in precarious socio-economic conditions, and are the poorest in Portugal and in the European Union (EU), as shown by the reports of the European Agency for Fundamental Rights (FRA). Despite national and European strategies, these situations continue, with the proliferation of racist demonstrations and hate crimes, and the growth of extreme right-wing parties. In 2022, the publication of a report by the FRA, regarding the situation of Roma in 10 EU countries (including Portugal), revealed the impact of antigypsyism in the areas of employment, education, health, and housing; these data triggered hate speech on social networks, which happens whenever something about Ciganos is published. A content analysis of the news disseminated by the main Portuguese media (press, TV, Radio) and of the comments on this news was conducted, through qualitative methodology. The results reveal racist hegemonic perspectives towards Ciganos: they depend upon the minimum income, do not contribute economically to the state accounts, and boast luxury goods.